2014
DOI: 10.1155/2014/541709
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lipocalin 2, Clusterin, Soluble Tumor Necrosis Factor Receptor-1, Interleukin-6, Homocysteine, and Uric Acid Levels in Patients with Psoriasis

Abstract: Background. Chronic inflammation may play a role in psoriasis pathogenesis. Lipocalin 2, clusterin, soluble tumor necrosis factor receptor-1 (sTNFR-1), interleukin-6, homocysteine, and uric acid are inflammatory and/or biochemical markers. However, both the roles of these markers and the pathogenesis of psoriasis are unknown. Objective. The aim of this study was to investigate serum levels of lipocalin 2, clusterin, sTNFR-1, interleukin-6, homocysteine, and uric acid in patients and controls groups. Methods. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…No correlation between lipocalin-2 and PASI was reported also by El-Hadidi et al, Kamata et al and Ataseven et al (13,14,20). On the contrary, Romani et al reported a positive correlation between LCN2 and PASI (8).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…No correlation between lipocalin-2 and PASI was reported also by El-Hadidi et al, Kamata et al and Ataseven et al (13,14,20). On the contrary, Romani et al reported a positive correlation between LCN2 and PASI (8).…”
Section: Discussionmentioning
confidence: 80%
“…Our results as well as values of serum lipocalin-2 concentrations are in accordance with few previous studies (8,14,20). Ataseven et al found significantly higher levels of lipocalin-2 in psoriatic patients compared with controls (p < 0.001) (14). The authors suggested that LCN2 could be used as a marker of the disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, they found a significant correlation between serum uric acid levels and PASI (11). As Ataseven et al mentioned in the limitations of their study, high serum uric acid levels may be related to components of metabolic syndrome (11). Therefore, the effect of metabolic syndrome components should be taken into account when investigating serum uric acid levels.…”
Section: Discussionmentioning
confidence: 90%
“…After the studies made in 1990s where high levels of homocysteine were found in plasma samples of subjects who had or would likely to have a history of myocardial infarction, ischemic stroke or peripheral vascular disease and the association of homocysteine with atherosclerosis and hypercoagulability had been shown [6][7][8][9][10][11][12] , along with increased attention to the comorbidities of psoriasis, as far as we know, 19 studies have been conducted to explore homocysteine levels in these patients. Homocysteine level was found to be high in 12 and normal in 7 of these studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Since this sulfur-containing amino acid is not taken through diet and not producing protein, homocysteine is formed via methionine catabolism 8,11,27 .…”
Section: Introductionmentioning
confidence: 99%